Boosting the Enforcement of EU Competition Law at the Domestic Level. - Looijestijn-Clearie, Anne (Cambridge Scholars Publishing : Cambridge Scholars Publishing, 2017)
The role of the EU competition law rules in shaping the EU Internal Market can hardly be overstated. The EU substantive rules dealing with cartels, abuse of dominance and State aid have ensured, in the past decades, a much desired unity of the law applied in the diverse European markets. Yet, much of the success of the EU competition law provisions depends on its practical enforcement. The proliferation of competition law enforcement, especially since 2004, stands testimony in this respect. However, this has not come without challenges. In this context, this book aims to critically discuss cer.